Psychological contract of tourism and hospitality professionals: Gap analysis - Lingadkar, Paresh R; Sankaranarayanan, Koloth Gangadharmenon (Journal of Tourism Management Research, 2023)
The purpose of the study is to explore the Psychological Contract of Tourism and Hospitality professional working in India. Using a well-designed and structured questionnaire, data linking pre-joining expectations and post-joining experience were captured on a five-point Likert scale. Descriptive statistics, mean analysis, gap analysis, factor analysis, and simple regression analysis were employed to draw conclusions about the data. Findings reveal that specific elements of the psychological contract among tourism and hospitality staff, namely, an attractive remuneration package, support in maintaining Work-Life balance, allowing adequate time to be spent with family, assigning a job profile that provides respect and dignity, and an environment free of power and politics, are considered important but are not fulfilled by the hospitality organizations. Employees are satisfied with a few aspects of the employment relationship, but overall satisfaction is negative. Four factors, namely 'work-life balance’, ‘freedom to’ ‘quit', 'rewards and acknowledgements’, and 'a safe and healthy working environment’, are the most significant and influential factors in predicting workers’ overall satisfaction. Amongst these, ‘Reward and Acknowledgement’ was the most significant factor in predicting workers’ overall satisfaction with their working organization. Human resource professionals must carefully and constantly recognize and monitor the psychological contract of tourism and hospitality professionals working in the Indian tourism sector. Tourism and hospitality organizations can benefit by effectively incorporating these factors into their human resource policies.